2015
DOI: 10.1128/jb.00415-15
|View full text |Cite
|
Sign up to set email alerts
|

A Periplasmic Complex of the Nitrite Reductase NirS, the Chaperone DnaK, and the Flagellum Protein FliC Is Essential for Flagellum Assembly and Motility in Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa is a ubiquitously occurring environmental bacterium and opportunistic pathogen responsible for various acute and chronic infections. Obviously, anaerobic energy generation via denitrification contributes to its ecological success. To investigate the structural basis for the interconnection of the denitrification machinery to other essential cellular processes, we have sought to identify the protein interaction partners of the denitrification enzyme nitrite reductase NirS in the periplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 61 publications
(63 reference statements)
1
24
0
Order By: Relevance
“…Very recently, NIR was also shown to control flagellum production and swimming motility under anaerobic conditions, independently from its ability to produce NO, by serving as a scaffold to form a ternary complex with the chaperone DnaK and the flagellar protein FliC in the periplasm (66). In the same study, the nirS mutant showed a partial restoration of swimming ability under aerobic conditions, whereas swarming mobility was previously shown to be affected under aerobiosis (63).…”
Section: Endogenous Sources Of No In P Aeruginosa and Their Effects supporting
confidence: 51%
See 1 more Smart Citation
“…Very recently, NIR was also shown to control flagellum production and swimming motility under anaerobic conditions, independently from its ability to produce NO, by serving as a scaffold to form a ternary complex with the chaperone DnaK and the flagellar protein FliC in the periplasm (66). In the same study, the nirS mutant showed a partial restoration of swimming ability under aerobic conditions, whereas swarming mobility was previously shown to be affected under aerobiosis (63).…”
Section: Endogenous Sources Of No In P Aeruginosa and Their Effects supporting
confidence: 51%
“…An intriguing possibility suggested by the latter study, which will require further investigation, is that NIR promotes motility in different ways, depending on oxygen availability, either by producing NO to increase rhamnolipid synthesis or activate other signaling pathways, or by directly controlling flagellum formation by protein-protein interactions. As underlined by Borrero-de Acuna et al (66), to fully understand these phenomena, the assembly of flagella under aerobic and anaerobic conditions will have to be analyzed in further detail. Since it is known that NO transcriptionally activates nirS expression, the production of a catalytically inactive version Ϫ ) is reduced to molecular nitrogen (N 2 ) in four reductive steps, each catalyzed by a specific reductase, namely, nitrate reductase (NAR), nitrite reductase (NIR), NO reductase (NOR), and nitrous oxide reductase (N 2 OR).…”
Section: Endogenous Sources Of No In P Aeruginosa and Their Effects mentioning
confidence: 99%
“…Afterward, the bacteria were dehydrated and subsequently embedded in Lowicryl K4M resin. After polymerization by ultraviolet light treatment, ultrathin sections were cut with a diamond knife, collected onto Butvar-coated nickel grids, and incubated with specific antibodies (44). First, sections were incubated with the first round of purified IgG antibodies overnight at 5°C.…”
Section: Methodsmentioning
confidence: 99%
“…The P. aeruginosa strains were grown to the exponential growth phase (optical density at 578 nm [OD 578 ] of 0.8). The protein complexes were cross-linked in vivo as previously described (44). Formaldehyde, used as the cross-linking agent, was injected into the anaerobic denitrifying culture in the late stationary phase to a final concentration of 0.125% (vol/vol).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation